Urban wetlands: wastelands or hotspots for conservation? Two case studies from Rome, Italy (Avocetta, 2017)
Urbanization is one of the main causes of the loss of wetlands today. Current urban planning and management rarely consider tthe value of wetlands despite the wide acknowledgement of the important ecosystem services they provide, particularly in terms of bio diversity conservation. Here, we provide data on bird communities wintering in two urban wetlands of the city of Rome, Italy, focusing on waterbirds and raptors in order to assess the importance of these areas for wildlife conservation and education. The field survey was conducted on January 2016 and January 2017. The first site comprised a section of the Tiber river and the surroundings open areas and host an average of 1041.5 ± 486.5 of birds belonging to 16 species of waterbirds and four raptor species. The other one is a flooded flint quarry where we counted an average of 440 ± 56 of birds belonging to 13 species of waterbirds and 3 species of raptors. Some species of conservation concern were regularly observed at both sites. Our results show the importance of these two sites for bird conservation but also for environmental education given their location inside the urban area of the largest Italian city.